Biochemical methane potential tests of different autoclaved and microwaved lignocellulosic organic fractions of municipal solid waste. (October 2016) - Pecorini, Isabella; Baldi, Francesco; Carnevale, Ennio Antonio; Corti, Andrea
Highlights: Autoclave and microwave pre-treatments are assessed before anaerobic digestion. Two synthetic OFMSW with different lignocellulosic contents are evaluated. Pre-treatments efficiency is tested on energy and methane production and solubility. Microwaving is found to be an efficient treatment for both the tested OFMSW. Autoclaving is more efficient for a richer lignocellulosic substrate. Abstract: The aim of this research was to enhance the anaerobic biodegradability and methane production of two synthetic Organic Fractions of Municipal Solid Waste with different lignocellulosic contents by assessing microwave and autoclave pre-treatments. Biochemical Methane Potential assays were performed for 21 days. Changes in the soluble fractions of the organic matter (measured by soluble chemical oxygen demand, carbohydrates and proteins), the first order hydrolysis constant kh and the cumulated methane production at 21 days were used to evaluate the efficiency of microwaving and autoclaving pretreatments on substrates solubilization and anaerobic digestion. Microwave treatment led to a methane production increase of 8.5% for both the tested organic fractions while autoclave treatment had an increase ranging from 1.0% to 4.4%. Results showed an increase of the soluble fraction after pre-treatments for both the synthetic organic fractions. Soluble chemical oxygen demand observed significant increases for pretreated substrates (up to 219.8%). In this regard, the mediocre results of methane's production led to the conclusion that autoclaving and microwaving resulted in the hydrolysis of a significant fraction of non-biodegradable organic substances recalcitrant to anaerobic digestion.